Improving water sustainability and food security through increased crop water productivity in Malawi - Nhamo, Luxon; Mabhaudhi, Tafadzwanashe; Magombeyi, Manuel Simba (MDPI, 2016)
Agriculture accounts for most of the renewable freshwater resource withdrawals in Malawi, yet food insecurity and water scarcity remain as major challenges. Despite Malawi’s vast water resources, climate change, coupled with increasing population and urbanisation are contributing to increasing water scarcity. Improving crop water productivity has been identified as a possible solution to water and food insecurity, by producing more food with less water, that is, to produce “more crop per drop”. This study evaluated crop water productivity from 2000 to 2013 by assessing crop evapotranspiration, crop production and agricultural gross domestic product (Ag GDP) contribution for Malawi. Improvements in crop water productivity were evidenced through improved crop production and productivity. These improvements were supported by increased irrigated area, along with improved agronomic practices. Crop water productivity increased by 33% overall from 2000 to 2013, resulting in an increase in maize production from 1.2 million metric tons to 3.6 million metric tons, translating to an average food surplus of 1.1 million metric tons. These developments have contributed to sustainable improved food and nutrition security in Malawi, which also avails more water for ecosystem functions and other competing economic sectors.